Desenvolvimento de processos hidrometalúrgicos para a reciclagem de metais de baterias de Ni-MH de telefones celulares - Santos, Vinicius Emmanuel de Oliveira dos (2012)
In this work, a hydrometallurgical method for the recovery of rare earth metals, cobalt, nickel, iron, and manganese from the negative electrodes of spent Ni-MH mobile phone batteries is developed. The rare earth compounds are obtained by chemical precipitation at pH 1.5 with NaCe(SO4)2.H2O and La2(SO4)3.H2O as the major recovered components. The composition and relative concentration of the chemical elements that constitute the recovered material are determined by inductively coupled plasma optical emission Spectroscopy (ICP-OES). This analysis confirms that the elements cobalt, nickel, iron, and manganese remain in solution after precipitation of the cerium and lanthanum. Iron is recovered as Fe(OH)3 and FeO. In addition, because manganese hydroxide precipitate initially undergoes an aging process in alkaline solutions and in the presence of oxygen, manganese is obtained as Mn3O4. Nickel and cobalt are recovered as ß-Ni(OH)2 and Co(OH)2. The recovered cobalt and nickel hydroxides are subsequently used to synthesize the cathode materials LiCoO2, LiNiO2 and CoO for use in Li-ion batteries. The anodes and recycled materials are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), fourier transform infrared spectroscopy (FT-IR), thermogravimetry (TG/DTG) and inductively coupled plasma optical emission spectroscopy (ICP-OES). Chemical and electrochemical recycling methods for the Ni, Co, Zn and Mn from the positives electrodes of spent Ni-MH batteries were developed. The materials recycled by chemical precipitation has the composition ß-Ni(OH)2, Co(OH)2, Zn(OH)2 and Mn3O4. The powder retains, sulphate, nitrate and carbonate anions from the mother solution as well as adsorbed water. Studies using cyclic voltammetry show that the current density decreases for scan rates greater than 10 mV s-1 because of the formation of hydroxide films. The amounts of Ni2+, Co2+, Zn2+ and Mn2+ were obtained by analysis of the solution using the inductively coupled plasma with optical emission spectroscopy technique, which demonstrated that the electrodeposition method exhibits anomalous behavior. The amount of deposited nickel ions is related to the composition of the sulfamate bath. The presence of manganese in the electrodeposits is due to the precipitation of Mn(OH)2, and Zn(OH)42- does not undergo reduction in the investigated potential range. The electrodeposited material contains Ni, Co, CoO, Co(OH)2, and Mn3O4. A charge efficiency of 83.7% was attained for the electrodeposits formed by the application of -1.1 V vs. Ag/AgCl at a current density of -90 C cm-2. The dissolution of the electrodeposits depends on the applied potential